Reduced Susceptibility to Azoles in Cryptococcus gattii Correlates with the Substitution R258L in a Substrate Recognition Site of the Lanosterol 14-?-Demethylase (2023)
Cryptococcus neoformans and Cryptococcus gattii cause cryptococcosis, a lifethreatening fungal infection affecting mostly immunocompromised patients. In fact, cryptococcal meningitis accounts for about 19% of AIDS-related deaths in the world. Because of long-term azole therapies to treat this mycosis, resistance to fluconazole leading to treatment failure and poor prognosis has long been reported for both fungal species. Among the mechanisms implicated in resistance to azoles, mutations in the ERG11 gene, encoding the azole target enzyme lanosterol 14-a-demethylase, have been described. This study aimed to establish the amino acid composition of ERG11 of Colombian clinical isolates of C. neoformans and C. gattii and to correlate any possible substitution with the in vitro susceptibility profile of the isolates to fluconazole, voriconazole, and itraconazole. Antifungal susceptibility testing results showed that C. gattii isolates are less susceptible to azoles than C. neoformans isolates, which could correlate with differences in the amino acid composition and structure of ERG11 of each species. In addition, in a C. gattii isolate with high MICs for fluconazole (64 mg/mL) and voriconazole (1 mg/mL), a G973T mutation resulting in the substitution R258L, located in substrate recognition site 3 of ERG11, was identified. This finding suggests the association of the newly reported substitution with the azole resistance phenotype in C. gattii. Further investigations are needed to determine the exact role that R258L plays in the decreased susceptibility to fluconazole and voriconazole, as well as to determine the participation of additional mechanisms of resistance to azole drugs.